Pengaruh Kompetensi, Motivasi dan Iklim Organisasi terhadap Kinerja Guru SDIT Assalam Islamic School Jeunieb Kabupaten Bireuen - Fhadil, Abdullah; Arief Syarifuddin, Evi (peusangan, 2023)
The research aims to analyze the influence of teacher competency, motivation and organizational climate at SDIT Assalam Jeunieb Islamic School, Bireuen Regency on teacher performance. Both partially and simultaneously. The research objects were 35 teachers as respondents with research instruments in the form of questionnaires and data analysis methods using multiple regression. The research results are known partially; (1) Competency influences teacher performance. 2) Motivation has a significant effect on teacher performance, and (3) Organizational climate has a positive effect on teacher performance. (4) Meanwhile, simultaneously aspects of competence, motivation and organizational climate have a significant effect on teacher performance at SDIT Assalam Jeunieb Islamic School, Bireuen Regency, amounting to 21.13%.